Spermatozoa Quality of Bali Cattle Following Sexing using Egg Yolk Tris Medium at Different Duration - Kesumanengsih, Viny Aprilia; Aka, Rahim; Saili, Takdir (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The length of sexing duration may affect the quality of Bali cattle spermatozoa. This study aims to examine the effect of sexing duration on viability, motility and abnormalities of Bali cattle spermatozoa. This research has been carried out at Regional Technical Implementation Unit (RTIU) Center for Breeding and Animal Feed, Department of Food Crops and Livestock, Southeast Sulawesi Province. The material used was a bull of Bali cattle as a source of semen and spermatozoa to be evaluated. In this study, a completely randomized design (CRD) was used with 3 treatments and 6 replications. The treatments consisted of three different length of sexing duration namely 40 min. (P1), 50 min. (P2), and 60 min. (P3). The variables evaluated in this study included semen quality (volume, color, odor, consistency and pH) and spermatozoa (mass movement, concentration, percentage of motility, viability and abnormalities). The data obtained were analyzed using analysis of variance (ANOVA) and continued with the Least Significant Difference test (LSD test). The results showed that the average volume of Bali cattle semen obtained was 5,38 ml/ejaculate, semen color was milky white, odor was specific, consistency was viscous, pH was 6,3, spermatozoa concentration was 1,445 million/ml and mass movement was +++. Whereas the motility of spermatozoa in each treatment following sexing were 76,67% (P1), 68,23% (P2), and 60,00% (P3).  The viability of spermatozoa after sexing were 93,42% (P1), 84,42% (P2), and 79,83% (P3). The abnormality of spermatozoa after sexing were 2,58% (P1), 2,67% (P2), and 2,67% (P3).  Furthermore, the results of variance analysis showed that the length of sexing duration had a significant effect (P˂0.05) on the viability and motility of the Bali cattle spermatozoa, but did not significantly affect the sperm abnormalities of Bali cattle. The 40 min. (treatment P1) and 50 min. (treatment P2) of sexing duration resulted in better spermatozoa viability and motility of Bali cattle compared to 60 min. (treatment P3) of sexing duration.Keywords:  abnormality, motility, sexing, spermatozoa, viability